Pocket warming of bupivacaine with fentanyl to shorten onset of labor epidural analgesia: A double-blind randomized controlled clinical trial. - Tyler M Balon; Yun Xia; Johnny McKeown; Jack Wang; Justin J Abbott; Marilly Palettas; Alberto Uribe; Marco Echeverria Villalobos; John C Coffman; Ling-Qun Hu (PLoS ONE)
Shortening analgesic onset has been researched and it has been documented that prewarming epidural medications to body temperature (37°C) prior to administration increases medication efficacy. Our double-blind randomized controlled trial was designed to investigate if a lower degree of prewarming in providers' pockets could achieve similar results without the need of a bedside incubator. A total of 136 parturients were randomized into either the pocket-warmed group or the room temperature group to receive 10 mL of 0.125% bupivacaine with 2 μg/mL fentanyl epidural bolus at either the 27.8 ±1.7°C or 22.1 ±1.0°C temperatures, respectively. Primary outcome, time to analgesic onset (verbal rating scale pain score ≤ 3) was recorded in 0-, 5-, 10-, 15-, 20-, 30-, and 60-minutes intervals. It was observed that the pocket-warming group (n = 64) and room temperature group (n = 72) had no significant difference of analgesic onset time (median 8 vs. 6.2 minutes; p = 0.322). The incidence of adverse events such as hypotension, fever (≥ 38°C), nausea, vomiting, and number of top-off epidural boluses, as well as patient satisfaction rates and mode of delivery, were not significantly different between the groups as well. Further research is warranted to confirm these findings and explore the impact of different temperatures on analgesic onset time as well as the logistical issues associated with their clinical implementations.